Development of seamless woven node element structures for application in integral constructions. Issue 11 (July 2016) - Fazeli, Monireh; Hübner, Matthias; Lehmann, Theo; Gebhardt, Ulrike; Hoffmann, Gerald; Cherif, Chokri
In order to advance consistent lightweight construction principles in automotive and mechanical engineering, support frame construction made from high-performance materials is becoming more commonplace. These consist of complexly structured nodular connection elements. The required connection elements have not yet been produced satisfactorily. The developed node element structures in this paper are produced on a shuttle weaving loom by flattening and weaving them as multi-surface woven fabrics. The development of the woven concept for the realization of node element structures is based on the fragmentation of the individual sub-elements. The goal of this research is development of a flexible technology for weaving fabrics and intended for the integral realization of woven nodular semi-finished products with complex geometries and connections, which are to be used to connect Fiber-reinforced Plastic components in support frame structures.